Between role and expression: Conjunction analysis and its pedagogical implication in teaching writing - Tobias Gunas; Hieronimus Canggung Darong (PT. MAWAMEDIA JAYAMUSTA BUANASIHA, 2025)
This qualitative study used a combination of linguistic and rhetorical analysis to look at how conjunctions are used in Donald Trump and Joe Biden's victory speeches. Grounded in a Systemic Functional Linguistics (SFL) theory, this article examined the functional features of language in the social context of political speech. The result of analysis shows distinctive patterns in conjunction choices that include locative, additive, contrastive, purpose-driven, simultaneous, sequential, conditional, and causal roles. While Trump's speech stresses additive and simultaneous structures, reflecting his dynamic and emotive rhetorical approach, Biden's speech lens toward purposeful conjunction, in line with a policy-oriented communication style. In the meantime, some types of conjunctions are absent prompts a reflection on implicit messages. Overall, by raising students' awareness of conjunction usage and its rhetorical impact in persuasive discourse, this study offers a nuanced exploration of language choices and advances our understanding of how conjunctions function within the larger context of political communication. This has potential pedagogical implications for ELT, particularly in the teaching of writing.